A crititcal analysis of the law regulating trade in genetically modified organisms from a South African perspective - Hennessy, Candace Natasha (Department of Commercial Law, 2014)
With the dawn of Genetically Modified Organisms (GMO's), humanity discovered the pathway to a future which before, only science-fiction movies had contemplated. GMO technology has made it possible to engineer plants, animals and other organisms to bear specific, desired characteristics, by manipulating the genetic structure of the organism in question, making it capable of unprecedented commercial use and humanitarian benefit in the form and manner desired by the genetic engineer. GMO's can possess properties which make them cheaper and easier to produce, or make them capable of specific functions ' from rendering consumer products more attractive, to alleviating hunger in desperately poor areas.